The Effect of Doped TiO2 Layer on the Performance and Stability of PCDTBT: PCBM-based Organic Solar Cells - Al-hashimi, Mohammed K.; Abdulameer, Ameer F.; Banimuslem, Hikmat A. J.; Rahaq, Yaqub (Iraqi Journal of Science, 2024)
Charge extraction layers play a crucial role in developing the performance of the inverted organic solar cells. Using a transparent metal oxide with appropriate work function to the photoactive layer can significantly decrease interface recombination and enhance charge transport mechanism. Therefore, electron selective films that consist of aluminium-doped titanium dioxide (TiO2:Al) with different concentrations of Al (0.4, 0.8, and 1.2)wt %  were prepared using sol-gel technique. The inverted organic solar cells PCPDTBT: PCBM with Al doped TiO2 as electron extraction layer were fabricated. It is well known that Al doping concentration potentially affects the physical characteristics of the TiO2 by controlling the optical, morphological, and structural properties. The effect of Al incorporation on the optical and morphological properties of the prepared films were analysed using UV-Vis spectroscopy, atomic force microscopy (AFM), X-ray diffraction (XRD), and scanning electron microscopy (SEM). The current–voltage (J-V) curves of the PCPDTBT: PCBM organic solar cells show that the TiO2:Al layer with 0.8% Al wt%, has the highest power conversion efficiency which is 3.02%.